Some aspects of restricted multi-trait sire evaluation of dairy cattle - SETHI, I C (The Indian Journal of Animal Sciences, 2014)
For ideal dairy cattle improvement programme multi-trait models are the natural choice. Restricted multi-trait models ensure non-occurrence of genotypic depression in component traits. Some practical aspects of these multi-trait models for sire evaluation with equality and inequality constraints are examined in the present Paper. These models are quite robust against imprecise estimates of genetic and environmental correlations between component traits and also to substantial degree ornon-orthogonality in the data.